Nutritional changes in germinated legumes and rice varieties - Azlan, Azrina; Amom, Zulkhairi; Megat Radzi, Megat Rusydi; C. W., Noraliza (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Proximate content and fatty acid composition of germinated and non-germinated legumes (kidney, mung, soy bean and peanut) and rice varieties (red, black, Barrio, brown and milled) were evaluated. In germinated samples, moisture content increased significantly while carbohydrate, protein and fat were decreased significantly. Total dietary fibre was increased in germinated samples except germinated kidney and mung bean. Germination also increased saturated fatty acids (SFA) in legumes, black, red and brown rice. Monounsaturated fatty acids (MUFA) decreased in all samples except germinated kidney, soy and Barrio rice. Polyunsaturated fatty acids (PUFA) increased in some germinated samples (mung bean, peanut, red, brown, Barrio and white rice) but decreased in other legume and rice samples. Generally, palmitic acid increased while stearic, oleic and linoleic acids decreased after germination. Overall, the proximate content and fatty acids of legume and rice varieties changed after germination and may be used as alternate resources for individuals with lifestyle diseases.